Teaching Social Scripts to Improve Social Communication for Students With Autism Spectrum Disorder. (May 2022) - Scheibel, Gretchen; Ma, Zijie; Travers, Jason C.
Students with Autism Spectrum Disorder are likely to demonstrate social impairments that contribute to challenging behaviors and academic difficulties. As a result, the task of improving social communication skills is a critical component to any educational program for this population. Scripting provides an evidence-based and versatile option for improving social communication, yielding valuable results while requiring limited time and resource preparation from educators. In this article, we present step by step guidance to support practitioners in using scripting interventions. Considerations are discussed for adapting this intervention to meet the needs of students across the autism spectrum and links to resources for strengthening implementation and including other evidence-based practices.